2019
DOI: 10.1177/1077559518821730
|View full text |Cite
|
Sign up to set email alerts
|

“She Wanted to Know the Full Story”: Children’s Perceptions of Open Versus Closed Questions

Abstract: The authors are grateful to the children and parents who participated, and to Belinda Guadagno for assistance with data collection and analysis for the pilot study. Parts of the paper were

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…Sharing views on open questions freely increases children's experiences of being listened to (Brubacher, Timms, Powell, & Bearman, 2019). By analysing children's negative experiences, we pay attention to the issues that children dislike and that need improvement, to increase knowledge about possible jeopardizing negative experiences in ECEC.…”
Section: Methodsmentioning
confidence: 99%
“…Sharing views on open questions freely increases children's experiences of being listened to (Brubacher, Timms, Powell, & Bearman, 2019). By analysing children's negative experiences, we pay attention to the issues that children dislike and that need improvement, to increase knowledge about possible jeopardizing negative experiences in ECEC.…”
Section: Methodsmentioning
confidence: 99%
“…Andersson-Bakken (2015) claims what is most important for the classroom dialogue is to follow up both open and closed questions with in-depth questions. Brubacher et al (2019) found that children tend to find closed questions easier than open questions because they require less reflection to answer, but also that they feel more listened to and better able to give their stories in response to open question. Mapplebeck and Dunlop (2021) revealed that when students were discussing open questions, two characteristics were important to them: they made them think, and they were made to work out answers for themselves.…”
Section: Research Articlementioning
confidence: 97%
“…Typical questions in this study that combine scaffolding of science content (SS) & science language (SL) placed in questioning model (Adapted from Ulleberg & Solem, 2018) teachers enabled participation by bringing out student ideas and expectations. Brubacher et al (2019) found that children feel more listened to and better able to give their stories in response to open questions. Prior knowledge and experiences as well as ideas were highlighted, which is an important part of activating and idea-generating dialogues (Kolstø, 2016).…”
Section: Orienting and Influencing Teacher Questions When Students Pr...mentioning
confidence: 98%
“…En este sentido, Wolfman, Brown y Jose (2016) estudiaron la capacidad de respuesta de víctimas de AS de 6 a 16 años en función del tipo de pregunta, y observaron que la probabilidad de obtener respuesta es mayor en las preguntas cerradas frente a las abiertas. Esto puede deberse a una mayor facilidad de respuesta percibida al requerir menor reflexión, aunque estas generen menor sensación de escucha (Brubacher et al, 2019).…”
Section: Fase De Recuperaciónunclassified